2008
DOI: 10.3349/ymj.2008.49.3.366
|View full text |Cite
|
Sign up to set email alerts
|

The Role of CD4+CD25bright Regulatory T Cells in the Maintenance of Pregnancy, Premature Rupture of Membranes, and Labor

Abstract: PurposeThe aim of this study was to evaluate the changes of the regulatory T cell subset in peripheral blood caused by gestational age and premature rupture of membranes (PROM) with or without labor to verify the role of regulatory T cells in pregnancy.Patients and MethodsWe investigated regulatory T cell distribution in the peripheral blood of pregnancies during the first trimester (group I, n = 2), the second trimester (group II, n = 12), and the third trimester without PROM and labor (group III, n = 15). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 18 publications
3
21
0
Order By: Relevance
“…Tregs significantly decline at term, probably in response to the onset of labor. This agrees with the recent observations of changes in Treg functions in preterm labor deliveries (Seol et al , 2008; Xiong et al , 2010; Schober et al , 2012). …”
Section: Uterine Nk Cells and Tregs In Pregnancy: Why Are They There supporting
confidence: 93%
“…Tregs significantly decline at term, probably in response to the onset of labor. This agrees with the recent observations of changes in Treg functions in preterm labor deliveries (Seol et al , 2008; Xiong et al , 2010; Schober et al , 2012). …”
Section: Uterine Nk Cells and Tregs In Pregnancy: Why Are They There supporting
confidence: 93%
“…98,99 It has been observed that immunotherapy of women with URPL using paternal mononuclear cells could cause reduction and increase, respectively, in levels of Th17 and Treg cells. LIT induces production of anti-paternal cytotoxic antibodies (APCAs), mixed lymphocyte reaction blocking antibodies (MLR-Babs or MLR-BF), and anti-idiotypic antibodies (Ab2) that can cover paternal human leukocyte antigen (HLA) in the surface of the fetus and thereby prevent from maternal natural killer (NK) and T cells attacking.…”
Section: Lit For Patients With Rplmentioning
confidence: 99%
“…The CD4+CD25+ Treg cells levels in peripheral blood lymphocytes of women suffering from URPL are lower than non-pregnant healthy women, which implies possible contribution of these cells in tolerance of maternal immune to conceptus antigens and thus conservation of pregnancy. 98,99 It has been observed that immunotherapy of women with URPL using paternal mononuclear cells could cause reduction and increase, respectively, in levels of Th17 and Treg cells. 100 Treg cells apply their function partially through secretion of anti-inflammatory cytokines such as IL-10…”
Section: Lit For Patients With Rplmentioning
confidence: 99%
“…Most studies observed an augmentation of Treg in peripheral blood and decidua during the first and second trimester in normal pregnant women (Heikkinen et al 2004;Xiong et al 2013;Tilburgs et al 2006). In the third trimester, Treg levels begin to decrease (Seol et al 2008) and further decline with successive stages of labor (Xiong et al 2010). Furthermore, Treg suppressive capacity is reduced in term labor and preterm labor suggesting that changes in Treg function may contribute to initiation of labor (Kisielewicz et al 2010).…”
Section: Regulatory T Cells In Human and Murine Pregnancymentioning
confidence: 99%